APPROACH AND METHODS OF THE 2016 ALASKA NATIVE HEALTH RESEARCH FORUM - Hiratsuka, Vanessa Y. (Am Indian Alsk Native Ment Health Res, 2018)
Southcentral Foundation, a tribal health organization serving Alaska Native and American Indian (AN/AI) people in southcentral Alaska, convened the Alaska Native Health Research Forum (Forum) for AN/AI people in May 2016. The purpose of the Forum was to obtain AN/AI community member feedback about sharing health research results. This article describes the funding mechanism that provided resources for the Forum and other factors that were considered when designing the Forum. This is followed by a description of how attendees were invited, the audience response system, and process used to collect quantitative data on participants and qualitative feedback from small group discussions with Forum attendees. Finally, we describe the quantitative and qualitative data analysis processes used to evaluate responses.